The Relationship between Age and Knowledge of Breast Care during Pregnancy at PMB Luluk Ester - Keswara, Nila Widya; Tiyas, Ani Widianing (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2025)
Breast care during pregnancy is highly recommended. There are many benefits for both pregnant women and their babies. Breast care during pregnancy (trimester 3) increases the production of breast milk needed by newborns. Adequate breast milk maximizes the growth and development of babies and minimizes the occurrence of nutritional deficiencies in children. Because breast milk is the main source needed by babies until the first 6 months of birth. Breast care during pregnancy also minimizes breast swelling due to the presence of breast milk dams in the breasts, this occurs because of blockages in the nipples that are not cleaned and cause mastitis. In this study, a survey was conducted on patients at PMB Luluk Ester. In this study, socialization was also carried out on the importance of breast care during pregnancy. It is hoped that all ages of pregnant mothers can know about how to care for their breasts. From the results of the questionnaire, the p value was obtained as much as 0.000 (p> 0.05). So it can be concluded that there is a relationship between age and knowledge of breast care during pregnancy.